Effectiveness of an exposure-based return-to-work program for workers on sick leave due to common mental disorders: a cluster-randomized controlled trial - Noordik, Erik; van der Klink, Jac J.; Geskus, Ronald B.; de Boer, Michiel R.; van Dijk, Frank JH; Nieuwenhuijsen, Karen (Scandinavian Journal of Work, Environment & Health, 2013)
' ' OBJECTIVES ': 'In case of long-term sick leave, gradually increasing workload appears to be an effective component of work-directed interventions to reduce sick leave due to common mental disorders (CMD). CMD are defined as stress-related, adjustment, anxiety, or depressive disorders. We developed an exposure-based return-to-work (RTW-E) intervention and evaluated the effect on time-to-full return to work (RTW) among workers who were on sick leave due to CMD in comparison to those treated with care-as-usual (CAU). CAU is guideline-directed and consists of problem-solving strategies and graded activities. ' ' METHODS ': 'Using a two-armed cluster-randomized trial, we randomized 56 occupational physicians (OP). Of these, 35 OP treated 160 workers at the start of their sick leave; 75 workers received RTW-E and 85 workers received CAU. These workers were followed over a 12-month follow-up period. The time-to-full RTW lasting ≥28 days without recurrence was the primary outcome measure. To evaluate differences between groups, we used intention-to-treat and multilevel Cox’s regression analysis. ' ' RESULTS ': 'The median time-to-full RTW differed significantly between groups [hazard ratio (HR) 0.55; 95% confidence interval (95% CI) 0.33–0.89]. The workers receiving RTW-E (209 days; 95% CI 62–256) had a prolonged time-to-full RTW compared to workers receiving CAU (153 days; 95% CI 128–178). ' ' CONCLUSIONS ': 'Workers on sick leave due to CMD treated with RTW-E showed a prolonged time-to-full RTW compared to those treated with CAU. We recommend that OP do not apply RTW-E but continue counseling workers on sick leave due to CMD according to CAU.
Keywords: absenteeism; common mental disorder; exposure; occupational health; randomized controlled trial; return to work; return-to-work program; RTW; sickness absence